Strengthening immunology literacy: an adaptable curricular framework for enhancing undergraduate immunology education - Sethman, Chad R.; Collins, Kelly J. R. (Frontiers in Education, 2025)
The rapidly expanding knowledge base in immunology and its increasing significance in multiple research areas and healthcare underscore the need for more comprehensive undergraduate curricula that allow students to engage deeply with immunology-based content. A robust immunology curriculum will provide undergraduate students a solid foundation for successful careers in research and healthcare. Unfortunately, there are few undergraduate programs in the United States that focus on core Immunology principles. This translates to deficits in Immunology education for medical students, graduate students, career scientists, and healthcare professionals. The Immunology and Medical Microbiology (IMMB) Bachelor of Science program at West Virginia University offers undergraduate students a comprehensive education in immunology and associated disorders. In pursuit of this degree, undergraduate students are required to take at least two laboratory-based and three lecture-based immunology courses. Although there is a need to enhance Immunology education and literacy, we recognize that doing this presents challenges in most undergraduate institutions and curricula. Therefore, we wanted to identify the most salient immunology topics from our three lecture-based immunology courses – Principles of Immunobiology, Cellular Immunobiology, and Molecular Immunobiology — that are most useful for professionals in both the research and healthcare sectors. Based on survey responses from IMMB alumni and current IMMB seniors, we provide a curricular framework that can be highly adaptable and serve as a model for institutions looking to enhance immunology education within their respective degree programs.